The Effectiveness of non-Judge Mediators in Settlement of Divorce Cases in Elderly Cases at the Bantul Religious Court - Mifta Zulfalah Azzahro; Miftahul Huda (Innovative: Journal Of Social Science Research, 2023)
The non-judge mediator refers to a party outside the court (not a judge) as a third party that has the rights to help the disputing parties in negotiating without any neutral case. This study aims to uncover the fact of the effectiveness level of the role of non-judge mediators in settling the divorce case in elderly cases in Religious Court Bantul. This is the qualitative field research, conducted at the Religious Court Bantul from February to March conducted analytically, and by taking data based on the findings in the field with a juridical-empirical approach based on the current law. i.e. PERMA Number 1 of 2016. The data were collected through observation, interviews, and documentation.The results of this study showed that first, the role of non-judge mediators in the implementation of mediation at the Religious Court Bantul has been in line with PERMA Number 1 of 2016, although it is not quite effective in settling the divorce cases. Based on data obtained in 2020, of 29 cases of elderly divorce, it was only 3 cases successfully settled by mediation. Second, the low rate of success in mediation in Religious Court Bantul was caused by several factors, including: very limited time, the constancy of the parties to get divorced, the prolonged problems faced by the parties, the absence of goodwill from the parties not attending the mediation process.